ChemInform Abstract: Gold‐Catalyzed Three‐Component Spirocyclization: A One‐Pot Approach to Functionalized Pyrazolidines. Issue 24 (27th May 2016) - Wagner, Bernd; Hiller, Wolf; Ohno, Hiroaki; Krause, Norbert
Abstract: The efficient approach involves the coupling of alkynols, hydrazines and various aliphatic and aromatic aldehydes/ketones via cycloisomerization of the alkynol to an exocyclic enol ether and subsequent [3+2]cycloaddition of an azomethine ylide.